Effect of Different Modified Atmosphere Packaging on the Quality of Mulberry Fruit (Morus alba L. cv Kokuso 21). (4th February 2021) - Tinebra, Ilenia; Sortino, Giuseppe; Inglese, Paolo; Fretto, Silvia; Farina, Vittorio
Abstract : The control of temperature and gas composition is essential to maintain the fresh flavor and quality of perishable fruits like mulberry. This study presented a modified atmosphere experiment (MAP) for fresh fruit showing the potential benefits of innovative gas mixing with argon. The effects of MAP were studied on the physicochemical and qualitative attributes of mulberry preserved at 4 ± 1 °C and 90 ± 5 % R.H. Fresh mulberries were packaged with different gas combinations: MAP1 (4%O2 +6%CO2 +90%N2 ), MAP2 (10%O2 +5%CO2 +85%Ar), CTR1 (20.9%O2 +0.04%CO2 ), and CTR2 (10%O2 +5%CO2 +85%N2 ). Changes in quality parameters were evaluated after 0, 4, 8, and 12 days of storage. Mulberries packaged with MAP had a lower weight loss than CTR samples which lost more than 80% of their initial weight. Furthermore, the results showed that the argon treatment was the best in keeping the fruit juice content, preserving its structure. Despite not showing great differences with MAP1 treatment, Ar allowed to maintain high TSS up to 8 storage days, slowed CO2 production. The sensory profile of mulberry fruit was not significantly affected by storage in modified atmospheres, and the production of potential unpleasant odors in MAP2 could not be perceived. The results of this study confirm that this innovative approach, using MAP technology, has a potential use in maintaining mulberry fruit quality for a longer time.